2013
DOI: 10.1016/j.febslet.2013.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences between the closed and open states of channelrhodopsin‐2 as observed by EPR spectroscopy

Abstract: Edited by Richard CogdellKeywords: Optogenetic Rhodopsin Light-activated cation channel Photocycle Membrane protein EPR spectroscopy a b s t r a c tChannelrhodopsin is a cation channel with the unique property of being activated by light. To address structural changes of the open state of the channel, two variants, which contain either 1 or 2 wild-type cysteines, were derivatised with nitroxide spin label and subjected to electron paramagnetic resonance spectroscopy. Both variants contained the C128T mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 32 publications
9
77
0
1
Order By: Relevance
“…By a combination of different time-resolved fluorescence techniques, we have presented results that lend support to the helix tilt model (5,(11)(12)(13) of helix B upon formation of the open channel state and gave insight in the possible mechanism by comparing the CrChR2 data with time-resolved anisotropy data from other retinal proteins. Accessibility studies revealed a pH-dependent structural heterogeneity close to the inner gate.…”
Section: Iafmentioning
confidence: 64%
See 4 more Smart Citations
“…By a combination of different time-resolved fluorescence techniques, we have presented results that lend support to the helix tilt model (5,(11)(12)(13) of helix B upon formation of the open channel state and gave insight in the possible mechanism by comparing the CrChR2 data with time-resolved anisotropy data from other retinal proteins. Accessibility studies revealed a pH-dependent structural heterogeneity close to the inner gate.…”
Section: Iafmentioning
confidence: 64%
“…A key role for helix B in light-induced channel opening and closing has been suggested. Evidence for light-induced movements of helix B is based on structural studies using electron crystallography and EPR spectroscopy (double electron-electron resonance) (11)(12)(13). Although double electron-electron resonance measurements suggest a light-induced displacement/outward tilt of helix B (11,13), electron crystallographic studies found additional evidence for a loss of order in that helix (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations